2015
DOI: 10.1016/j.apjtm.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Is there a way out for the 2014 Ebola outbreak in Western Africa?

Abstract: The 2014 Ebola outbreak in West Africa, primarily affecting Guinea, Sierra Leone, and Liberia, has exceeded all previous Ebola outbreaks in the number of cases and in international response. Although infections only occur frequently in Western Africa, the virus has the potential to spread globally and is classified as a category A pathogen that could be misused as a bioterrorism agent. This review aims (i) to discuss the latest data to aid our current recommendations for the prevention and control of the Ebola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As in prior studies from both Africa and the United States/Europe, we found the most common signs/symptoms of EVD to be very non-specific, including headache, anorexia, myalgias/arthralgias, fever, weakness, and gastrointestinal symptoms. [ 4 , 16 23 ] Less common signs/symptoms included dyspnea, conjunctivitis, dysphagia, non-hemorrhagic rash, hiccups, cough, and bleeding. While hemorrhage has been a prominent feature in previous outbreaks, we found bleeding to be one of the least frequently observed symptoms, present in less than ten percent of patients at triage and in about a third of patients at some point during their illness.…”
Section: Discussionmentioning
confidence: 99%
“…As in prior studies from both Africa and the United States/Europe, we found the most common signs/symptoms of EVD to be very non-specific, including headache, anorexia, myalgias/arthralgias, fever, weakness, and gastrointestinal symptoms. [ 4 , 16 23 ] Less common signs/symptoms included dyspnea, conjunctivitis, dysphagia, non-hemorrhagic rash, hiccups, cough, and bleeding. While hemorrhage has been a prominent feature in previous outbreaks, we found bleeding to be one of the least frequently observed symptoms, present in less than ten percent of patients at triage and in about a third of patients at some point during their illness.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Since it first outbreaks in 1976, there has been around a million of suspected and laboratory-confirmed cases of EVD reported in Africa, making it persistently exposed to the EVD. [13][14][15][16][17] Besides, self-defense and self-care are of utmost importance for selfsafety and overall national safety. 18,19 Although in Malaysia, EVD is not yet prevalent but due to its contagious nature, it can be a big future threat that may turn into a pandemic or an epidemic threat for the country.…”
Section: Introductionmentioning
confidence: 99%
“…9,28 This transmission can occur through several channels and across multiple hosts as shown in Figure 1.…”
Section: Mode Of Transmissionmentioning
confidence: 99%
“…29 After an incubation period of about 2-21 days, EVD is characterized by early non-specific symptoms which may resolve in some survivors, or may progress to a full blown hemorrhagic syndrome. 9,28,37 In the early stages of the disease it is characterized by constitutional symptoms which make it's diagnosis even more difficult. 21 The first symptom which manifests is fever of >38 o C in about 85-95% of patients, this is the most common symptom followed by other non-specific symptoms such as headaches (52-74%), general malaise (85-95%), difficulty in swallowing and sore throats (56-58%), while about 26% of patients experience dry cough.…”
Section: Signs and Symptomsmentioning
confidence: 99%